Sociology of Medicine: Gender Problems of the Competitiveness of Women Dentists - Margaryan, Edita (Journal of Sociology: Bulletin of Yerevan University, 2020)
Modern medicine is developing in a society in which special attention is paid to the quality of services provided, including dental services. At the same time, there are gender stereotypes that impede the full realization of the possibilities of women dentists as professionals, which directly affects the state of this field of medicine as a whole. The study of gender imbalance and the development of measures to improve the competitiveness of female dentists in the modern labor market are relevant at all stages of the organization and provision of dental services. The article reveals gender problems and stereotypes in the dental services market through a sociological survey of practicing doctors.
Keywords: sociology of medicine; dentistry; dentist; gender problems; stereotypes; inequality